Morphologic patterns of nodal reactive hyperplasia in primary organ malignancy-architectural changes and evaluation by comparison with other morphological parameters - Singh, Preeti; Singh, Neha; Jaiswal, Vijay Kumar; Verma , Nidhi (International Journal of Research in Medical Sciences, 2023)
Background: Reactive lymph node hyperplasia can exhibit morphological patterns I to VI. This study was done to evaluate lymph node hyperplasia, lymph node reactive patterns, lymph node metastasis and correlation with tumour stage, lymph node patterns and lymph node size. Methods: Total 454 lymph nodes were reviewed for metastases and reactivity patterns I to VI as per the World Health Organization (WHO) protocol. Association between qualitative variables was assessed by the chi-square test and Fisher’s exact test, those between quantitative variables using unpaired t-test. Results: Lymph node hyperplasia was highest in breast and commonest lymph node reactive patterns were lymphocyte predominance, germinal centre predominance, sinus histiocytosis and mixed patterns. Conclusions: Lymph node hyperplasia and lymph node reactive patterns show organ-wise variation and need standardisation. Most common lymph node reactive patterns included lymphocyte predominance and germinal centre predominance hyperplasia. Studying lymph node reactivity may help to understand host immune reaction against the tumour and thus influence prognosis.